De novo variants in GREB1L are associated with non-syndromic inner ear malformations and deafness - Schrauwen, Isabelle; Kari, Elina; Mattox, Jacob; Llaci, Lorida; Smeeton, Joanna; Naymik, Marcus; Raible, David W.; Knowles, James A.; Crump, J. Gage; Huentelman, Matthew J.; Friedman, Rick A. (Human genetics, 2018)
Congenital inner ear malformations affecting both the osseous and membranous labyrinth can have a devastating impact on hearing and language development. With the exception of an enlarged vestibular aqueduct, non-syndromic inner ear malformations are rare, and their underlying molecular biology has thus far remained understudied. To identify molecular factors that might be important in the developing inner ear, we adopted a family-based trio exome sequencing approach in young unrelated subjects with severe inner ear malformations. We identified two previously unreported de novo loss-of-function variants in GREB1L [c.4368G>T;p.(Glu1410fs) and c.982C>T;p.(Arg328*)] in two affected subjects with absent cochleae and eighth cranial nerve malformations. The cochlear aplasia in these affected subjects suggests that a developmental arrest or problem at a very early stage of inner ear development exists, e.g., during the otic pit formation. Craniofacial Greb1l RNA expression peaks in mice during this time frame (E8.5). It also peaks in the developing inner ear during E13–E16, after which it decreases in adulthood. The crucial function of Greb1l in craniofacial development is also evidenced in knockout mice, which develop severe craniofacial abnormalities. In addition, we show that Greb1l −/− zebrafish exhibit a loss of abnormal sensory epithelia innervation. An important role for Greb1l in sensory epithelia innervation development is supported by the eighth cranial nerve deficiencies seen in both affected subjects. In conclusion, we demonstrate that GREB1L is a key player in early inner ear and eighth cranial nerve development. Abnormalities in cochleovestibular anatomy can provide challenges for cochlear implantation. Combining a molecular diagnosis with imaging techniques might aid the development of individually tailored therapeutic interventions in the future.